Effects of dietary xylooligosaccharide on growth, digestive enzymes activity, intestinal morphology, and the expression of inflammatory cytokines and tight junctions genes in triploid Oncorhynchus mykiss fed a low fishmeal diet - Chang’an Wang (Elsevier, 2022)
The purpose of this study was to show how dietary xylooligosaccharides (XOS) affect growth and intestinal digestive enzyme activity, histology, inflammatory cytokines, barrier function gene expression, and microbiota of juvenile rainbow trout (Oncorhynchus mykiss). Different diets (G1, G2, G3, G4, and G5) containing graded levels of XOS (0, 2.5, 5.0, 7.5, and 10.0 g/kg) were fed to triplicate groups of 30 fish (initial average weight 20.85 ± 0.48 g) for 56 days. The fish fed 10 g/kg XOS had significantly improved weight gain (P < 0.05). Intestinal lipase and amylase activity were significantly improved (P < 0.05). Intestinal histology in the height of the villi was also significantly improved (P < 0.05). TNF-alpha factor (TNF-α) and interleukin 6 (IL-6) were significantly lower in G4–G5 than that in G1 (P < 0.05); Interleukin 10 (IL-10), claudin-1, and ZO-1 showed the opposite trend. Dietary XOS altered the intestinal bacterial composition. At the phylum level, dietary XOS supplementation resulted in a decrease in abundance of the Proteobacteria in G2 and G5 treatments. At the genus level, compared to the control group, the genus Lactobacillus showed an increase with dietary XOS supplementation in G3–G5 treatments. Overall, feeding juvenile triploid O. mykiss 5.0–10.0 g/kg XOS improved growth and intestinal health by promoting intestinal development, limiting intestinal damage and inflammation, and regulating the community structure of the intestinal microbiota.